Assessing the European Union Science Diplomacy towards India 2009–2013 – From an Experimental Pilot Initiative into a Political dialogue - Myllymäki, Ilkka (fi=Turun yliopisto|en=University of Turku|, 2016)
This thesis examines the European Union (EU) as an actor in science diplomacy during the years 2009–2013. The study links the science and technology policy (S&T) literature with the study of EU global actorness by offering a new cross-disciplinary approach to analyze the EU’s external policy in the S&T domain. The author performs an empirical case-study analysis utilizing core concepts from European studies literature and European integration history. The focus lies on the policy evolution of the first pilot initiative of the Strategic Forum for International S&T cooperation of the European Union (SFIC). The SFIC was created as an advisory group under the European Research Area framework to assist the European Commission and the Council of the EU in the field of international S&T cooperation. The SFIC initiated during its first years a pilot initiative with India which ultimately developed into a political dialogue and declarations between the European Commission, several EU member states and India, for the first time in history. This thesis assesses the main characteristics of the initiative and the role of different actors in the process with an historical contextualization. The thesis finds that the EU’s science diplomacy with India was shaped and formulated at advisory group level, evolving from an experimental pilot initiative into a political partnership. Main characteristics of this policy shaping process were effective coordination of different national S&T policies based on voluntary participation between the EU member states and the European Commission. Jointly set objectives in the advisory group led to a coherent external policy and enabled the European Union to speak with a single voice. It was the first time when the European Commission and the EU member states together conducted political dialogue with a third country in the field of international science and technology cooperation. SFIC India Pilot Initiative is also regarded as a successful example of EU external policy-making, and it served as a precedent for consequent S&T pilot initiatives with other emerging economies. The thesis concludes that the EU is a global actor and soft power in science diplomacy with the member states being the most important actors in the policy making process.